2007
DOI: 10.1097/yic.0b013e3280148c19
|View full text |Cite
|
Sign up to set email alerts
|

Do differences in atypical antipsychotics matter in routine practice? Medication switch from olanzapine and risperidone to amisulpride

Abstract: Atypical antipsychotics are often addressed as one class of drugs, although there are marked differences in their pharmacological profiles. It is unknown how this is seen by practitioners and to what extent they differentiate between the various atypical compounds. In a drug utilization study, 472 schizophrenic outpatients who were switched for individual reasons from either olanzapine or risperidone to amisulpride were monitored. Data on patients, illness and treatment as well as on reasons to switch were col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
7
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 23 publications
1
7
0
Order By: Relevance
“…Although this study is limited by potential selection biases, the survey results indicate that most EU4 European psychiatrists perceived differentiation in atypical antipsychotics as a class in terms of efficacy and tolerability; this finding is in keeping with the current literature [33][34][35][36][37][38] . Conversely, only a minority reported a difference in the SSRIs as a class.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…Although this study is limited by potential selection biases, the survey results indicate that most EU4 European psychiatrists perceived differentiation in atypical antipsychotics as a class in terms of efficacy and tolerability; this finding is in keeping with the current literature [33][34][35][36][37][38] . Conversely, only a minority reported a difference in the SSRIs as a class.…”
Section: Discussionsupporting
confidence: 71%
“…Avoiding specific side effects, prior treatment/failed history, patient non-adherence and the presence of specific clinical symptom(s) or co-morbidities are common reasons for prescribing a sequential range of antipsychotics to treat patients with schizophrenia or bipolar disorder 34,[36][37][38]40 .…”
Section: Discussionmentioning
confidence: 99%
“…48 In a recent drug use survey, the 2 most common reasons for practitioners to switch from olanzapine to amisulpride treatment included weight gain and expectancy of less weight gain with amisulpride. 49 In our study, patients who had been treated previously with the -pine group SGAs showed a faster and greater weight (and also BMI) reduction than those who had been treated previously with -done group SGAs. Our study provides further evidence that weight reduction associated with switching SGA treatments may be related to the class of the prior SGA treatments.…”
Section: Discussionmentioning
confidence: 88%
“…Furthermore, a large meta-analysis has shown comparable efficacy for risperidone, olanzapine, and amisulpride 8. However, it should be noted that patients switching from risperidone and olanzapine due to poor tolerability often do so for different reasons (risperidone due to extrapyramidal side effects and olanzapine due to concerns about weight gain) and that the two groups of pretreated patients in this study may have an inherent selection bias based on each group’s profile of reasons for switching medication, which was unfortunately not recorded as part of the ESCAPE study 10,32. In addition, the analysis included a higher number of patients who switched from risperidone vs olanzapine, and the small patient number overall may have influenced this result.…”
Section: Discussionmentioning
confidence: 97%
“…Furthermore, the incidence of extrapyramidal side effects in patients switching from risperidone was slightly higher than previous reports from two studies of amisulpride conducted in France by Carrière et al36 (23%) and Colonna et al33 (13%). However, it is known that patients more frequently discontinue risperidone due to extrapyramidal side effects and olanzapine due to concerns about weight gain 8,10,32. Therefore, it may be that patients switching from risperidone were already experiencing extrapyramidal side effects before initiation of amisulpride, which is also evidenced by the higher use of concomitant therapy for this side effect in these patients vs patients switching from olanzapine or the treatment-naïve patients.…”
Section: Discussionmentioning
confidence: 99%